Role of antioxidants in the treatment of hepatocellular carcinoma: Integrative review (Research, Society and Development, 2021)
Theorical framework: Hepatocellular carcinoma is a unique cancer that typically arises in the setting of chronic liver disease at a rate dependent upon the complex interplay between the host, disease, and environmental factors. Unfortunately, with contemporary management, patients with advanced hepatocellular carcinoma have few treatment options, and the prognosis is poor. Objective: Evaluate the role of antioxidants in the treatment of hepatocellular carcinoma. Methodology: It is an integrative review, with a qualitative approach. Based on research on ScienceDirect and PubMed databases, 12 articles were selected that were consistent with the theme and the inclusion and exclusion criteria, through the association of descriptors and keywords. Results: Studies in vivo demonstrated a positive correlation of antioxidants in the treatment of hepatocellular carcinoma. The antioxidants were able to promote inhibition of development tumor through promotes decrease of proinflammatory cytokines IL-1 and IL-6 and changes the ratios of Bax/Bcl2 that supports apoptosis. In oxidative stress, may be able to direct free radical scavenging activity. Among the main antioxidants with advanced preclinical evidence in the treatment of hepatocellular carcinoma is curcumin with tests in humans, and gallic acid, quercetin and resveratrol with several tests in vitro and in vivo. Conclusion: This study highlights that antioxidants can be a promising therapy in the treatment of hepatocellular carcinoma.